Initial soil community drives heathland fungal community trajectory over multiple years through altered plant-soil interactions - Radujković, Dajana; van Diggelen, Rudy; Weijters, Maaike; Harris, Jim A.; Pawlett, Mark; Verbruggen, Erik; Bobbink, Roland; Vicca, Sara (Wiley, 2019)
•Dispersal limitation, biotic interactions and environmental filters interact to drive plant and fungal community assembly, but their combined effects are rarely investigated. •This study examines how different heathland plant and fungal colonization scenarios realized via three biotic treatments ‐ addition of mature heathland derived sod, addition of hay and no additions ‐ affect soil fungal community development over six years along a manipulated pH gradient in a large‐scale experiment starting from an agricultural, topsoil removed state. •Our results show that both biotic and abiotic (pH) treatments had a persistent influence on the development of fungal communities, but that sod additions diminished the effect of abiotic treatments through time. Analysis of correlation networks between soil fungi and plants suggests that the reduced effect of pH in the sod treatment, where both soil and plant propagules were added, might be due to plant‐fungal interactions since the sod additions caused stronger, more specific, and more consistent connections compared to no addition treatment. •Based on these results, we suggest that the initial availability of heathland fungal and plant taxa, that reinforce each other, can significantly steer further fungal community development to an alternative configuration, overriding otherwise prominent effect of abiotic (pH) conditions.
Keywords: fungal community development; biotic interactions; soil pH; plant-fungal networks; heathland restoration; ITS1